APPLICATION OF WIRELESS SENSORS FORSTRUCTURAL HEALTH MONITORING AND CONTROL - Pritika Holey; Harshal Nikam (International Engineering Journal For Research & Development, 2020)
Wireless sensors have been suggested for use in structural health monitoring systems.As they offer low-installation costs and automated data processing facility. To authenticate the concert of the proposed wireless modular monitoring system on the vibration measurement of large-scale civil structures, a three-story half-scale steel structure is instrumented with a wireless monitoring system assembled from a network of six wireless sensors and tested it on a shaking table to ensure the consistency of the data communication. Field application of WiMMS to ambient vibration survey of Gi-Lu cable-stayed bridge is examined. Finally, the preliminary study on structural control using MR-damper through WiMMS is also open.